Properties and environmental impact of the mosaic sludge incorporated into fired clay bricks - Sarani, Noor Amira; Abdul Kadir, Aeslina; Abdul Rahim, Ahmad Shayuti; Mohajerani, Abbas (Elsevier Ltd, 2018)
This paper presents fundamental information on the utlization of mosaic sludge waste from industrial mosaic activities into building materials. The study greatly benefits solid waste management and industries that produce waste with high heavy metal concentration by providing insights on ways to dispose waste by minimizing heavy metal leaching potential whilst providing a new formulation of low-cost and environmentally friendly building materials. Therefore, an alternative disposal method is to incorporate mosaic waste such as bodymill sludge (BS) and polishing sludge (PS) into fired clay brick. The bricks were incorporated with different percentages (0%, 1%, 5%, 10%, 20% and 30% by weight) of sludge waste and fired at 1050 C (0.7 C/min heating rates). The optimization results showed that the incorporation of up to 30% of mosaic sludge into fired clay bricks is capable of improving its physical and mechanical properties. Moreover, the incorporation of mosaic sludge waste into clay bricks has a positive effect on firing shrinkage, density and compressive strength. However, a decreased performance was reported for certain aspects. Hence, this study demonstrated that BS and PS can be alternative low-cost and environmentally friendly which can be used to improve the physical and mechanical properties of fired clay bricks.